Nutrition Effect on Iron, TIBC and Albumin Level in Underweight Pregnant Women for Preventing Underweight Baby - Rahajoe Imam Santosa; Natalia Yuwono; Etha Rambung; Ferdinand Aprianto Tannus; Abednego Nugraha; Salmon Charles P. T Siahaan (Lambung Mangkurat, 2022)
According to data from the Indonesian Ministry of Health (2018) stunting is the nutritional problems for children under age of five, where in 2017 about 22.2% children under five experienced stunting. Indonesia is the third country with the highest prevalence stunting in Southeast Asia, where the average in 2005-2017 was 36.4% (WHO). This study focused on providing micronutrient supplements to pregnant women with CED for the prevention of stunting in newborns. Aims to analyze differences in maternal weight, anemia states, albumin levels and albumin levels before and after micronutrient administration. This study used an experimental pre and post test with randomization in the group of pregnant women with CED in Made Surabaya sub-district. Results: Weight comparison (P < 0.001) was significant; Comparison of LILA (P < 0.001) was significant; The ratio of Hb (P < 0.001) was significant; Albumin ratio (P < 0.001) was significant; The ratio of serum iron (P = 0.015) was significant; TIBC comparison (P = 0.004) was significant. In this study, the results of comparative analysis of CED pregnant women were given micronutrient supplementation and without administration, where in the analysis of body weight, LILA, Hb, Albumin, Serum iron and TIBC showed significant differences.